CORRELATION BETWEEN BRAIN MAGNETIC RESONANCE IMAGING CHANGES AND CLINICAL PROGRESSION OF AMYOTROPHIC LATERAL SCLEROSIS - Stomnaroska, Daniela Ristikj; Veljanovski, Dimitar; Petrovski, Darko; Cvetkovska, Daniela; Lazarova, Eleonora; Aleksovska, Angela (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Amyotrophic lateral sclerosis is a progressive neurodegenerative disease, with clinical symptoms and signs of central and peripheral motor neuron damage. Research objectives: to find a correlation between brain changes verified by magnetic nuclear resonance with the degree of progression of the neurodegenerative disease.Material and methods : A total of 15 patients were included in the study, who underwent a clinical and neurological examination; electromyography, neuroimaging studies (MR of the brain and spinal cord), examination of a panel of paraneoplastic antibodies in order to exclude a paraneoplastic etiology of the disease, and lumbar puncture with cytochemical analysis and electrophoresis of the cerebrospinal fluid.Results: signal changes of the corticospinal tracts were seen in two patients, in whom the clinical picture was dominated by bulbar symptomatology. Conclusion: brain parenchyma changes recorded by the magnetic nuclear resonance are not a specific indicator of disease progression. Keywords: magnetic resonance imaging, amiotrophic lateral sclerosis.